2017
DOI: 10.1021/acscentsci.7b00156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of the Specific Anticancer Property of Artemisinin and Its Combination with Aminolevulinic Acid for Enhanced Anticolorectal Cancer Activity

Abstract: The antimalarial artemisinin (ART) possesses anticancer activity, but its underlying mechanism remains largely unclear. Using a chemical proteomics approach with artemisinin-based activity probes, we identified over 300 specific ART targets. This reveals an anticancer mechanism whereby ART promiscuously targets multiple critical biological pathways and leads to cancer cell death. The specific cytotoxicity of ART against colorectal cancer (CRC) cells rather than normal colon epithelial cells is due to the eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 65 publications
(163 reference statements)
4
72
1
2
Order By: Relevance
“…Our previous studies demonstrated that ART activates lysosomal function and induces autophagy in HCT116 and HeLa cells, which is attributed to the suppression of mTOR activity. It was also reported that ART induces autophagy in chondrocytes through the increase of Beclin1 expression and the decrease of PI3K, AKT, and mTOR phosphorylation, indicating the suppression of the PI3K‐AKT‐mTOR pathway.…”
Section: Signaling Pathways and Cellular Targets Involved In Autophagmentioning
confidence: 94%
See 3 more Smart Citations
“…Our previous studies demonstrated that ART activates lysosomal function and induces autophagy in HCT116 and HeLa cells, which is attributed to the suppression of mTOR activity. It was also reported that ART induces autophagy in chondrocytes through the increase of Beclin1 expression and the decrease of PI3K, AKT, and mTOR phosphorylation, indicating the suppression of the PI3K‐AKT‐mTOR pathway.…”
Section: Signaling Pathways and Cellular Targets Involved In Autophagmentioning
confidence: 94%
“…In vivo, many human tumor xenograft models also show the anticancer effect of artemisinin in both subcutaneously and orthotopically transplanted tumors . Similar to the activation of artemisinin in malaria, the high levels of free heme synthesized in the mitochondria of cancer cells leads to the activation of artemisinin's anticancer properties . Using a synthesized mitochondria‐targeted probe called artemisinin‐triphenylphosphonium bromide (artemisinin‐TPP), we observed increased potency of the anticancer effect of artemisinin‐TPP compared with that of the parent compound .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[11,12] ¾hnliche Untersuchungen wurden von Ismail et al durchgeführt. Wang et al haben vor kurzem eine Vielzahl von Artemisinin-bindenden Proteinen von Plasmodium falciparum entdeckt.…”
unclassified